Analisis Kinerja Kantor Kesyahbandaran dan Otoritas Pelabuhan (KSOP) terhadap Kelancaran Aktivitas Bongkar Muat di Pelabuhan Tanjung Balai Karimun - Jeri Haswanda; Zakwan Hilmy (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Ports play a strategic role in supporting the smooth flow of national logistics; therefore, the operational performance of port authorities is a crucial factor in loading and unloading activities. This study aims to analyze the role and performance of the Port Authority and Harbormaster Office (KSOP) in supporting the smoothness of loading and unloading activities of steel cargo vessels at Tanjung Balai Karimun Port. The research employs a descriptive qualitative approach, with data collected through field observations, interviews, and documentation during an internship program at KSOP Tanjung Balai Karimun. Primary data were obtained from observations of 35 steel cargo vessels with a total cargo volume of 42,000 tons, interviews with KSOP officers, port operators, and shipping agents, as well as operational documentation. Secondary data were derived from KSOP operational reports, the Inaportnet system, and relevant literature. The results indicate that KSOP performance has a significant influence on the smoothness of loading and unloading activities, as reflected by an Effective Time to Berth Time (ET/BT) ratio of 62.4%, an average vessel waiting time of 0.85 hours, and a loading and unloading productivity rate of 26 tons per hour. Operational efficiency is supported by effective coordination among KSOP, port operators, and shipping agents; however, several constraints remain, including limited supporting facilities and potential administrative delays. This study concludes that optimizing digital-based service systems and strengthening inter-agency coordination are key strategies to improving loading and unloading performance at Tanjung Balai Karimun Port..